Toxicidade de Extratos Botânicos de Fabácea e Rubiácea para Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) - Costa, Daniel de Carvalho Melo (2015)
It is important to find new products front of problems related to the use of synthetic pesticides, accordingly, the plant secondary metabolites are shown quite promising. Thus, in this study aimed to evaluate the effects of leaves extracts and stem bark from the species Copaifera langsdorffii, Coussarea hydrangeifolia, Guettarda angelica and Rudgea viburnoides for the caterpillars of Spodoptera frugiperda in assay with and without choice. It was estimated the median lethal concentration (LC50) of each collected plant parts. Thus, the aqueous extracts were added to artificial diet at concentrations 1%, 2%, 4% and 6% (v/v) and offered to the caterpillars 1 st instar. Mortality was assessed daily until the pupal stage. For the second assay, the aqueous extracts of these plants were added to the artificial diet at concentration on the LC50 and offered to the caterpillars 1 st instar of S. frugiperda. Survival every 24 hours until the end of insect cycle was evaluated. After 10 days from the trial begin it was evaluated caterpillars weight; every 48 hours until 16th day the caterpillars weigh; fecal weight, quantification of proteins in the feces and food intake on 16th day; larval stage, pupal stage and survival and pupae weight were carried out. At the adult’s emergence, couples were individualized and evaluated: the sex ratio, longevity, number of postures eggs, and egg viability of the second day of posture, periods of pre-oviposition and oviposition of each couple. Food intake in the larval stage was reduced by aqueous leaves extracts of C. langsdorffii, C. hydrangeifolia, G. angelica and bark of R. viburnoides, C. langsdorffii, C. hydrangeifolia and G. angelica. All aqueous extracts reduced caterpillars weight gain over time. Aqueous extracts from the leaves of selected plants have increased the protein amount excreted in the feces of S. frugiperda except G. angelica. To adult stage, only the barks extract of G. angelica reduced the oviposition period, whereas the other biological characteristics have not changed. In the essay with a free choice, the barks aqueous extract of C. hydrangeifolia, R. viburnoides and leaves of C. hydrangeifolia and R. viburnoides showed anti-feed activity. From these results the plants selected for the work have potential for control of S. frugiperda, and the barks extract and the leaves of C. hydrangeifolia were more toxic to fall armyworm.